KEEFEKTIFAN MEDIA LITERACY INTERACTIVE FLASHCARD TERHADAP KOMPETENSI MEMAKNAI KOSAKATA BAHASA INDONESIA DI KELAS IV SEKOLAH DASAR - Abdul Gani, Pradanawan; Yoga Prihatin; Sutji Muljani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Vocabulary mastery is a crucial component of literacy and significantly influences the ability to comprehend reading texts. However, elementary school students often encounter difficulties in interpreting new vocabulary found within texts. This study aims to determine the effectiveness of Literacy Interactive Flashcard (Litraflash) media in enhancing the Indonesian vocabulary interpretation skills of fourth-grade students. A quantitative approach was employed using a quasi-experimental method with a pretest–posttest control group design. The research subjects consisted of two fourth-grade classes at an elementary school in Talang District, Tegal Regency, assigned as the experimental and control groups, respectively. Data were collected through pretest and posttest instruments that had been validated and tested for reliability. Data analysis involved normality and homogeneity tests as prerequisites, followed by independent sample t-tests and N-Gain analysis. The results showed that the experimental group achieved an average N-Gain score of 0.61 (moderate–high category), while the control group achieved an average N-Gain score of 0.38 (moderate category). The t-test results indicated a significant difference between the two groups (p < 0.001). These findings demonstrate that Litraflash media is effective in improving the Indonesian vocabulary interpretation skills of fourth-grade elementary school students.